DAMPAK EFEKTIVITAS PENDIDIKAN TATA KRAMA DALAM KELUARGA TERHADAP PERTUMBUHAN KARAKTER ANAK DI SDK NAILEKU - Mones, Anselmus Yata; Tmaneak, Laurensia (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2021)
The purpose of this research is as a basis for educating children in the family about ethics, to be able to know the role of parents in teaching manners to children, to shape the child's personality into a person of character, and also as an inspiration for researchers about the importance of ethics for students. children, in achieving success towards the personal character. The findings of this study are that almost all parents teach manners at home. They say that it is very important to teach manners to children and needs to be instilled so that the child's personality can become a useful person in the family and society. Courtesy education in the family is very important for the growth of children's character at school. Manners are taught for the reason that later the child's personality can become a good person or a person of character. Because manners in the family are very important and must be taught from an early age so as not to have an impact on the family when they are adults. With karma, the child's personality can maintain the good name of the family, especially parents. Character education in the context of education in schools is a type of education whose main hope is the realization of students who have moral integrity that can be reflected in everyday life. These values ​​are manifested in good interaction behavior in relationships with God, relationships with others, and relationships with God. Character education is very important and must be instilled from childhood.